Registros públicos e transidentidade - perspectivas do terceiro gênero - Machado, Conceição de Maria de Abreu Ferreira (2019)
The understanding of transidentities, in the legal field, requires reflections on the categorization of gender, segregated from the biological notion of sex. Recognition of the vulnerability of subjective situations experienced by non-binary transgender entails a structural change in the public record for the recognition of self-perceived identity, without this affecting the breaking of the real truth. Based on the question of the scope of the use of the term "transgender", in the decision of the Federal Supreme Court, in ADI 4275-DF, to allow the mutability of sex and name in the civil registry, the present work investigates whether the protection of all forms of gender identity were protected or not. Thus, the research aims to verify the extension of ownership of the fundamental right to free development of the personality, based on the right to self-determination, in view of the diversity contained in the term of transgender, to analyze the effectiveness of the decision of the Supreme Court against the binary system of public records and to search for the affirmation of a third genre. The analysis approaches the openness to the expansiveness of fundamental rights, starting from the dimensional variants of the principle of the dignity of the human person, in order to allow the protection of new situations that demand constitutional protection, in the contemporary scenario marked by frantic cultural modifications. As a result of the promotion of the dignity of the human person in the legal system and the constitutionalization of civil law, the rights of the personality carry the affirmation of legal protection of the person, with the recognition of rights inherent to the intimate and social individuality. The methodology adopted uses the hypothetical-deductive method, with the purpose of verifying and contesting the presented hypotheses; in the phases of the research, the techniques of bibliographic, documentary and jurisprudential research are used.